ANTI-TUMOR ACTIVITY AND IMMUNE RESPONSES INDUCED BY HUMAN CANCER-ASSOCIATED MUCIN CORE PEPTIDE 1 - Ma, Yunguo; Yuan, Mei; Fei, Lihua; Li, Li (Chinese Journal of Cancer Research, 2013)
Objective: To investigate the immune responses induced by apomucin which is a mixture of mucin core peptide, in mice for elucidating the role of mucin core peptide in the modulation of cancers. Methods: Apomucin was isolated from human pancreatic cancer cell line SW1990. The mice were immunized with this apomucin (10μ/time×6) plus DETOX. Results: When immunized, all mice developed delayed-type hypersensitivity (DTH) after challenged with apomucin or synthetic peptide MUC-2 or MUC-3, while the mice immunized with apomucin alone did not develop DTH. No antibodies were detected by ELISA after immunization. When the spleen cells of vaccinated mice were cocultured with this apomucin (10--50μg/ml) and rhlL-2(50U/ml) in vitro, the proliferated lymphocytes showed cytotoxieity against human cancer cells, including colon cancer, gastric cancer, pancreatic cancer and leukemia as measured by Cr-51 release assay. Antibodies against MUC-2 and MUC-3 could block the cytotoxicity. Conclusion: It was identified that a vaccine combined of apomucin and immune adjuvant DETOX can induce cellular immune response and anti-tumor cytotoxicity in mice.